Recurrent Metastatic High-Grade Osteosarcoma: Disease Stabilization and Successful Pregnancy Outcome following Aggressive Multimodality Treatment - Khurana, Monica; Gruner, Barbara; Sathi, Bindu Kanathezhath (Indian Journal of Medical and Paediatric Oncology, 2018)
Prognosis for refractory/recurrent metastatic osteosarcoma (OS) remains dismal with 3-year survival rates <20%. Achievement of more than 5 years of stable, refractory/recurrent metastatic OS disease in our patient is itself unique and attributable to multimodality therapy. Her high-dose chemotherapy regimen with alkylating agents did not lead to infertility, making her case even more unique. Successful disease stabilization and pregnancy outcome in our patient with metastatic multiple relapsed OS is one of the first cases published. We need further understanding and exploration of pathogenesis, chemoresistant mechanisms, and multimodality therapies including immunotherapy for OS.
Keywords: Cancer therapy; fertility; osteosarcoma